Treatment-free remission in Chronic Myeloid Leukemia harboring atypical BCR-ABL1 transcripts. - Matteo Dragani; Jessica Petiti; Giovanna Rege-Cambrin; Enrico Gottardi; Filomena Daraio; Giovanni Caocci; Chiara Aguzzi; Elena Crisà; Giacomo Andreani; Francesca Caciolli; Carmen Fava (Mediterranean Journal of Hematology and Infectious Diseases)
Discontinuation of tyrosine kinase inhibitors (TKI) is the main goal today in the field of Philadelphia positive chronic myeloid leukemia (Ph + CML) and the criteria to attempt the interruption of therapy are well defined and rely on the possibility to regularly monitor the BCR-ABL1 transcript. Patients harboring atypical transcripts are automatically excluded from protocols due to the absence of a standardized method of quantification of their minimal residual disease (MRD). We report here the outcome of 6 patients with atypical transcripts with a long follow up whose MRD was followed in three cases with digital PCR during their treatment free remission (TFR).